Nanoelectronics Fundamentals Materials, Devices and Systems - Raza, Hassan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers the state of the art in the theoretical framework, computational modeling, and the fabrication and characterization of nanoelectronics devices. It addresses material properties, device physics, circuit analysis, system design, and a range of applications. A discussion on the nanoscale fabrication, characterization and metrology is also included. The book offers a valuable resource for researchers, graduate students, and senior undergraduate students in engineering and natural sciences, who are interested in exploring nanoelectronics from materials, devices, systems, and applications perspectives. .
Introduction -- Atomic Structure -- Electronic Structure -- Quantum Transport -- Charge based Devices. Spin based Devices -- Memories -- Circuits and Systems -- Nanofabrication -- Microscopy and Spectroscopy.
Keywords: Nanoscience; Microtechnology; Microelectromechanical systems; Nanotechnology; Semiconductors; Telecommunication; Nanophysics; Microsystems and MEMS; Nanotechnology; Semiconductors; Microwaves, RF Engineering and Optical Communications